Effect of ambience, food quality and price fairness on customers' loyalty: focus on Arabic food restaurants in Johor Bahru / Jurainah Ali, Hanis Amirah Roslin and Aidi Azhar Alias - Ali, Jurainah; Roslin, Hanis Amirah; Alias, Aidi Azhar (2022)
The Malaysian government immediately implemented the Movement Control Order (MCO) to break the COVID-19 chain and were impact to restaurants sector. However, based on the survey, it was found that the preference for Arabic Food Restaurant changed after post-Covid. Thus, the Theory of Loyalty was applied in this study to represent quality construct in the customers' loyalty model and help identify areas for further improvement. This study used the SWOT (Strength, Weakness, Opportunity and Threats) approach to analyse the issues at Arabic Food Restaurants. This study aims to determine how customers' loyalty to an Arabic Food Restaurants was impacted by factors such as ambiance, food quality, and price fairness. The approach of this study is a quantitative method using a structured questionnaire. A total of 400 questionnaire online forms were processed using the statistical tool SPSS to test the hypotheses that had been developed. In this study, finding shows that ambience, food quality and price fairness has strong relationship with customers' loyalty. All null hypotheses are accepted. Therefore, Arabic Food Restaurant owners need to allocate strategies focus on the ambience, food quality and price fairness as factors to cater customers' loyalty in order to compete with other rivals.